The role of gamma irradiation to induce genetic variability and improve the yield of groundnut (Arachis hypogaea L) - Hafsa Mesbahi; Imane Saibari; Mohammed Ezziyyani; Ahlam Hamim (Arab Journal of Basic and Applied Sciences)
Groundnut (Arachis hypogeae L) is very edible plant worldwide due to its richness inunsaturated oil. It is cultivated in different agroclimatic zones. The use of groundnut inrotations or intercropping is now considered as an alternative and sustainable way to improve agrosystems. The aim of this study was to evaluate the yield of two varieties (KP29 and flower 11) through the mutation induction using the Gamma rays (cobalt60) for 100, 150 and 200 Gy. Many parameters have been studied, morphologic, agronomic and quality parameters. the results have showed a significant difference for KP29 at 200 Gy for weight pods and seeds (p ˂ 0.05), however no significant difference have been showed for pods number and seed number (p > 0.05). The var.F11, have showed a significant difference for the four agronomic parameters (p ˂ 0.05). The results of this study showed that radio-mutagenesis succeeded in creating genetic variability in groundnut on M4 generation affecting morphological and agronomic characters, the change in color and shape of seeds and even the construction of pods was well marked concerning the two varieties studied.